Peran Dinas Pendidikan Dan Kebudayaan Dalam Menurunkan Angka Anak Putus Sekolah Di Kabupaten Bone Bolango - Dewi Humaira Maspeke; Fajriani As; Fasya Toliu; Jamila A. Pakaya; Moh. Wahyu Toana; Oktaviani Djibran; Siti Nurdea Ananda Putri Djafar; Sulistiawati Abdullah; Magvirah El Walidayni Kau (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Out-of-School Children (OOSC), school dropouts, and graduates who do not continue their education remain challenges in educational development in Bone Bolango Regency. This study aims to examine the role of the Bone Bolango Regency Office of Education and Culture in reducing the rates of OOSC, dropouts, and non-continuing graduates through the use of Verification and Validation (Verval) data from Pusdatin of the Ministry of Primary and Secondary Education and actual field conditions. The research employed a descriptive qualitative approach, using in-depth interviews with the Head of the Office of Education and Culture and Subdistrict Education Coordinators, supported by quantitative data from the Verval system. The findings indicate that the Office has implemented several efforts, including strengthening non-formal education services through community learning centers (PKBM), conducting data collection and community outreach, and planning affirmative programs such as scholarships and school uniform assistance. However, these efforts have not been fully effective due to data inaccuracies, weak cross-sector coordination, and the absence of a strong early detection system at the school level.